2008
DOI: 10.1002/jbm.a.31630
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte/macrophage interactions: Biomaterial surface‐dependent cytokine, chemokine, and matrix protein production

Abstract: The role of lymphocytes in the biological response to synthetic polymers is poorly understood despite the transient appearance of lymphocytes at the biomaterial implant site. To investigate cytokines, chemokines, and extracellular matrix (ECM) proteins produced by lymphocytes and macrophages in response to biomaterial surfaces, human peripheral blood monocytes and lymphocytes were co-cultured on polyethylene terephthalate (PET)-based material surfaces displaying distinct hydrophobic, hydrophilic/neutral, hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 45 publications
2
64
1
Order By: Relevance
“…However, the production of cytokines, chemokines, and extracellular matrix proteins were biomaterial surface chemistry dependent. [145] Utilizing the in vitro co-cultures and the transwell system for isolating paracrine interactions, lymphocytes, via paracrine and juxtacrine means, enhanced adherent macrophage/FBGC activation in terms of inflammatory cytokine production (unpublished results). Therefore, our laboratory has demonstrated that both direct (juxtacrine) and indirect (paracrine) mechanisms of interactions between lymphocytes and macrophages may play an integral part in the inflammatory, foreign body reaction, and wound healing events that occur at the tissue/material interface.…”
Section: Lymphocyte/macrophage Interactionsmentioning
confidence: 99%
“…However, the production of cytokines, chemokines, and extracellular matrix proteins were biomaterial surface chemistry dependent. [145] Utilizing the in vitro co-cultures and the transwell system for isolating paracrine interactions, lymphocytes, via paracrine and juxtacrine means, enhanced adherent macrophage/FBGC activation in terms of inflammatory cytokine production (unpublished results). Therefore, our laboratory has demonstrated that both direct (juxtacrine) and indirect (paracrine) mechanisms of interactions between lymphocytes and macrophages may play an integral part in the inflammatory, foreign body reaction, and wound healing events that occur at the tissue/material interface.…”
Section: Lymphocyte/macrophage Interactionsmentioning
confidence: 99%
“…Therefore, the production of cytokines by blood cells in biocompatibility studies has been widely investigated [40,41]. Even if Janský et al [17], who studied the dynamics of cytokine production in human PBMC, reported that many cytokines reach maximal levels after 4 or 12 or 24 h, other authors have chosen to assay cytokine production after longer times of incubation [19]. In our research, cytokine levels were determined after 48 h of culture, in order to refer the release of the cytokines to PBMC proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Also a biomaterial may induce the activation of macrophages, which, in an attempt to phagocytose it, secrete many inflammatory mediators, such as cytokines. Chang et al [19] investigated cytokines, chemokines, and extracellular matrix (ECM) proteins produced by lymphocytes and macrophages in response to biomaterial surfaces. These authors hypothesized that the production of inflammatory molecules from lymphocytes and macrophages in response to the contact with biomaterials could be modulated by the biomaterial surface chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…These findings provided insight into lymphocyte and macrophage interactions in response to biomaterial surfaces along with evidence consistent with the hypothesis that distinct surface chemistries modulate lymphocyte and macrophage interactions. Finally, a mechanistic model which would provide a tool for further analysis of lymphocyte and macrophage interactions in response to biomaterial surfaces and a step toward quantitative predictability of biomaterialdependent processes was presented [19]. Combinatorial techniques also help in protein biomaterial design [25].…”
Section: Protein Biomaterials Design and Implicationsmentioning
confidence: 99%